(untitled) (Fiep Bulletin - online, 2015)
The objective of the present study was to investigate the influence of a cerebral stimulation with auditory stimulations’ training program, in the motor learning and memorization, the learning of the bowling’s game. Had been selected 20 children with age band of 7 and 8 years old, in which Experimental Group (GE) and Control Group had been divided in (GC), having carried through GE a program of 36 sessions of Bowling’s training with duration of 45 minutes parallel to the cerebral stimulation with auditory stimulations’ training program with duration of 35 minutes. Already the GC only carried through the program of Bowling’s training with the same number of sessions and same duration. The data daily pay and after-program had disclosed that the Experimental Group in which used the program of a cerebral stimulation for auditory stimulations’ training, were significantly superior to the Group Control (p=0.05) in relation the performance in learning and memorization. One concludes that the here described results are substantial in that the interactivity says respect enters a program of a cerebral stimulation with auditory stimulations’ training and motor learning and memorization.